Fundamental concepts in the Cyclus nuclear fuel cycle simulation framework. (April 2016) - Huff, Kathryn D.; Gidden, Matthew J.; Carlsen, Robert W.; Flanagan, Robert R.; McGarry, Meghan B.; Opotowsky, Arrielle C.; Schneider, Erich A.; Scopatz, Anthony M.; Wilson, Paul P.H.
Highlights: Nuclear fuel cycle modeling generality and robustness are improved by a modular, agent based modeling framework. Discrete material and facility tracking rather than fleet-based modeling improve nuclear fuel cycle simulation fidelity. A free, open source paradigm encourages technical experts to contribute software to the Cyclus modeling ecosystem. The flexibility of the Cyclus tool from the simulator user perspective is demonstrated with both open and closed fuel cycle examples. Abstract: As nuclear power expands, technical, economic, political, and environmental analyses of nuclear fuel cycles by simulators increase in importance. To date, however, current tools are often fleet-based rather than discrete and restrictively licensed rather than open source. Each of these choices presents a challenge to modeling fidelity, generality, efficiency, robustness, and scientific transparency. TheCyclus nuclear fuel cycle simulator framework and its modeling ecosystem incorporate modern insights from simulation science and software architecture to solve these problems so that challenges in nuclear fuel cycle analysis can be better addressed. A summary of theCyclus fuel cycle simulator framework and its modeling ecosystem are presented. Additionally, the implementation of each is discussed in the context of motivating challenges in nuclear fuel cycle simulation. Finally, the current capabilities ofCyclus are demonstrated for both open and closed fuel cycles.